(untitled) (Kriminalističke teme, 2004)
According to Declaration of Steering committee Council for implementation of peace legislated 30 januara 2003, because of economic reforms in Bosnia and Herzegovina, to introduce united customs and tax administration and value added tax (VAT) on the state level to introduce importent part of this proces of reforms. In the same way European Community insists on this reforms. In this cease B&H legislated these laws and reforms: "Law of system indirect texation in B&H", with customs and tax-VAT on the state level, and to restore system of charge and distribution on budget of B&H, Federation, RS and District on the legal way. Management for indirect texation was established in Banja Luka with first president of steering committee mr. Joly Dixson. the management must have unique account for money distribution. Characteristics for application of VAT: With VAT there is a less way for tax evasion. Tax evasion is very popular in many firms: offshore,- non-existent for «laundry money», donlt pay tax etc. we are wearing for implementation of VAT bigining 2006, because it is very slouly and dificult procedure of implementation. Expect reforms in customs systems B&H: Unique customs administration on the state level, Organization of customs administration with organized customs house, officers, works.. . Establishing a system of information managing compatible with European Union in the aim of inter-connecting with ASYCUDA and rendering of high quality services customs procedures. Reforms of tax and customs systems will bring biger budget in this country and the level of corruption, smuggling and crime will be lower.